PEACEBUILDING PYRAMID: THE ROLE OF RELIGIOUS LEADERS IN POST-CIVIL WAR PEACE EFFORTS IN SOUTHERN SUDAN - Yenis Contesa; Ayu Dwi Tanti; Sarah Monica Benli (Prodi Ilmu Hubungan Internasional, Universitas Fajar, 2024)
This study aims to unveil the role of religious leaders in the civil war efforts in South Sudan. This research employed the peacebuilding pyramid approach proposed by Lederach. The data were obtained through literature studies from books, scientific articles, documents, online media, and official reports published by government and non-government institutions relevant to peacebuilding in South Sudan. The article argues that religious leaders have played an important role in peacebuilding efforts in South Sudan since the conflict emerged in 2013. This study revealed several findings; first, at the top leadership, religious leaders act as mediators between the two conflicting parties, marked by the success of the 2018 RARCSS agreement. Second, middle-range leadership focuses on mobilizing the community and advocating for peace. Third, in the grassroots leadership section, religious leaders focus their attention on counseling and empowering communities affected by war both directly and indirectly. Through the mapping of the peacebuilding pyramid model, the presence of religious leaders in the community has positively influenced the peace process in South Sudan. This paper contributes to peace studies using Lederach’s peacebuilding pyramid model approach.